Prevalence of COPD among Patients on Bronchodilator Therapy Presenting to a Tertiary Care Center - Mishra, Navin Kumar; Thakuri, HemaChand; Shrestha, Sareen; Rai, Utshav; Dhamala, Rasmita; Nepali, Rohit; Dahal, Suresh; Sha, Parmeshwar; Khadka, Gaurav; Lamichhane, Aayush; et al. (Nepalese Respiratory Journal, 2025)
Background: Chronic Obstructive Pulmonary Disease (COPD) is the most common non-communicable disease in Nepal and the third leading non-communicable disease globally. Despite its significant burden on public health, proper research is limited in local settings. Objective: This study aims to find out the utilization of spirometry in establishing the diagnosis of COPD. Method: A single-center, prospective, cross-sectional study design was conducted that included all patients more than 40 years old on bronchodilator therapy for COPD coming to the Pulmo OPD of Kathmandu Medical College Teaching Hospital (KMCTH). COPD was diagnosed by GOLD COPD. Criteria of fixed post-bronchodilator FEV1/FVC ratio <0.70. A Chhabra et al. 2014 reference equation from the North Indian population was taken for percentage prediction. Result: A total of 6789 patients visited the pulmo OPD. 877 (12.92%) patients were being treated for COPD at different centers. Out of 877 patients, only 371 cases (42.3%) were properly diagnosed with COPD followed by bronchodilator therapy, and 185 (21.09%) cases were mistakenly treated for COPD, i.e., overdiagnosis, as proven by spirometry later on. Among 692 COPD-confirmed patients, 380 (54.91%) were female and 312 (45.09%) were male. Conclusion: We conclude that a significant proportion of individuals who are on bronchodilators lack spirometry confirmation to diagnose COPD. Moreover, our study also shows a slightly increased prevalence of COPD among females.